2008
DOI: 10.1007/s10637-008-9155-y
|View full text |Cite
|
Sign up to set email alerts
|

Level of HER2/neu gene amplification as a predictive factor of response to trastuzumab-based therapy in patients with HER2-positive metastatic breast cancer

Abstract: Summary To explore the clinical significance of the level of HER2/neu gene amplification in a homogenous cohort of 33 patients with HER2-positive metastatic breast cancer (MBC) and available tumor samples treated with a trastuzumab-based regimen, we retrospectively performed dual-color fluorescence in-situ hybridization test and correlated them for each patient with time-to-progression (TTP) and overall survival (OS). We obtained values of HER2/chromosome 17 centromere (CEP17) ratio ranging from 2.5 to 21 (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…In recent studies, a positive correlation was even shown between the level of HER-2 amplification assessed by FISH and the rate of pathologic complete response to trastuzumab-based neoadjuvant treatment [36,37]. Also in gastric cancer, tumors with both amplification and overexpression recently showed better response to trastuzumab than cancers with overexpression alone.…”
Section: Discussionmentioning
confidence: 98%
“…In recent studies, a positive correlation was even shown between the level of HER-2 amplification assessed by FISH and the rate of pathologic complete response to trastuzumab-based neoadjuvant treatment [36,37]. Also in gastric cancer, tumors with both amplification and overexpression recently showed better response to trastuzumab than cancers with overexpression alone.…”
Section: Discussionmentioning
confidence: 98%
“…31 Surprisingly, however, the level of amplification has been proven so far to be truly outcome predictive only for neoadjuvant therapy. [32][33][34] With gastric cancer in the ToGA trial, a trastuzumab-based regimen was found more effective in patients with tumors highly expressing the ERBB2 protein. 4 A positive correlation between levels of gene amplification and overall survival after trastuzumabbased therapy has also been recently established.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, the role of HER2/neu in urinary bladder cancer is still unclear. A wide variability of HER2/neu gene amplification and of protein overexpression has been observed in TCC, associated with most advanced tumors and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%